2015
DOI: 10.1002/ajhb.22680
|View full text |Cite
|
Sign up to set email alerts
|

Altitude effect on birth weight and prematurity in the Province of Catamarca (Argentina)

Abstract: To be female appears to be a benefit under conditions of prematurity and high altitude. The increased incidence of prematurity due to altitude increase may reflect an adaptive advantage of preterm birth under these conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 18 publications
0
6
1
3
Order By: Relevance
“…High altitude has also been shown to adversely influence birth outcome . For instance, newborns at higher altitudes in Argentina were more likely to born preterm and at low birthweight than those born at lower altitudes . In addition, Han Chinese women who immigrated to Tibet were more likely to give birth to low‐birthweight newborns than women originally from Tibet , suggesting some physiological adaptation across generations .…”
Section: Discussionmentioning
confidence: 99%
“…High altitude has also been shown to adversely influence birth outcome . For instance, newborns at higher altitudes in Argentina were more likely to born preterm and at low birthweight than those born at lower altitudes . In addition, Han Chinese women who immigrated to Tibet were more likely to give birth to low‐birthweight newborns than women originally from Tibet , suggesting some physiological adaptation across generations .…”
Section: Discussionmentioning
confidence: 99%
“…In the province of Jujuy, and using the same source, Grandi et al 30 have demonstrated that the prevalence of prematurity, small for gestational age infants, and mild and severe intrauterine growth restriction are increasingly related to high-altitude; the latter two factors are even, significantly, twice as high in the Puna than in Maternidad Sardá, a maternity center located at sea level. Candelas et al 31 reach the same conclusion when analyzing birth weight in the province of Catamarca, and they establish that the increased incidence of preterm births caused by a higher altitude above sea level may account for an adaptive advantage of preterm delivery in these conditions. Finally, other cultural and physiological factors, which are related to one another, may account for the higher infant mortality observed in high-altitude environments.…”
Section: Discussionmentioning
confidence: 57%
“…Mothers who lived in the highlands with lower oxygen level risked her baby for hypoxic fetal syndrome that causes neonatal asphyxia and LBW [62]. Differences were found in birth weight based on sexes and in the incidence of low birth weight depending on altitude [63], while the findings Tibetan birth weights are greater than those of other ethnic groups, both at high and low altitudes. Tibetans at low altitudes have heavier birth weights compared with Tibetans at high altitude.…”
Section: Discussionmentioning
confidence: 93%